Cervical Spondylosis, Surgical Management and Outcome - Abbas, Emad S.; Mohammad, Yuksel Y. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Cervical spondylosis is a degenerative disease of the cervical spine and can occur at any age but mostly after 5th decade.Objectives:  is to focus a light on the clinical features, radiological findings and the result of the surgical treatment with comparison to the global results in the same field.Patients and method: This is a prospective study of 50 patients with cervical spondylosis managed with surgery at surgical specialty hospital in the medical city, Baghdad, from the period from Jun. 2011 till Jan. 2012. The clinical, radiological, neurophysiological studies together with surgical outcome were all reviewed and included in the study.Results: Patients were divided into two age groups; those below 50 years had their disease mostly of traumatic cause and their presentations were mostly of motor dysfunctions. Older patients had the disease process of degenerative cause and much slower progress and they were mostly complaining of sensory problems.Conclusions: Early surgery was the most beneficial in both groups, and bearded less morbidity to the patients.